Effect of a New Natural Seasoning on the Formation of Pyrazines in Barbecued Beef Patties - Javier García-Lomillo; Ma Luisa González-SanJosé; Raquel Del Pino-García; Miriam Ortega-Heras; Pilar Muñiz-Rodríguez (Journal of Chemistry)
The formation of pyrazines in food cooking is required to obtain satisfactory “roasted” flavor. The aim of this work was to evaluate the effect of a new red wine pomace seasoning (RWPS) on the formation of pyrazines in barbecued beef patties. Five pyrazines were successfully identified, 2,5-dimethylpyrazine being the most abundant. Although 2-ethyl-5-methylpyrazine was in lower levels, it presented the highest odor units, due to its low threshold. RWPS enhanced the formation of the five identified pyrazines (2.1 times), without relevant changes in the proportion between them. The highest increase was observed for 2-ethyl-6-methylpyrazine (3 times higher than in control). These results were corroborated by electronic nose analysis, presenting RWPS beef patties higher odor intensities. Mechanisms to explain these effects are also proposed in the present work, and the high content of polyphenols seems to be the major cause of the observed results. The use of RWPS could improve the flavor characteristics of meat products or enable using less intense cooking conditions with no changes in the flavor.